2006
DOI: 10.1186/1471-2458-6-80
|View full text |Cite
|
Sign up to set email alerts
|

Geography, private costs and uptake of screening for abdominal aortic aneurysm in a remote rural area

Abstract: Background: The relationship between geographical location, private costs, health provider costs and uptake of health screening is unclear. This paper examines these relationships in a screening programme for abdominal aortic aneurysm in the Highlands and Western Isles of Scotland, a rural and remote area of over 10,000 square miles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…However, 4.5% of men with an aortic diameter of 25-29 mm had a hospital admission with an aneurysm diagnosis during follow-up, such presentations becoming noticeable from two years after screening, supporting the concept of repeat screening in the 25-29 mm group. The association between aneurysm and cardiovascular disease that we observed has been shown in several studies 1618 19 In the Tromso study,15 an abdominal aortic aneurysm at baseline conferred a 2.5-fold increase in cardiovascular mortality over 10 years, compared with a 1.88-fold increased risk in our study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, 4.5% of men with an aortic diameter of 25-29 mm had a hospital admission with an aneurysm diagnosis during follow-up, such presentations becoming noticeable from two years after screening, supporting the concept of repeat screening in the 25-29 mm group. The association between aneurysm and cardiovascular disease that we observed has been shown in several studies 1618 19 In the Tromso study,15 an abdominal aortic aneurysm at baseline conferred a 2.5-fold increase in cardiovascular mortality over 10 years, compared with a 1.88-fold increased risk in our study.…”
Section: Discussionsupporting
confidence: 79%
“…The association between aneurysm and cardiovascular disease that we observed has been shown in several studies. 16 18 19 In the Tromso study, 15 an abdominal aortic aneurysm at baseline conferred a 2.5-fold increase in cardiovascular mortality over 10 years, compared with a 1.88-fold increased risk in our study. One study followed up 4734 men and women aged over 65 for 10 years.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…These results are based on analysis of change over two years and it is possible that lower educational groups are simply slower to take up new services and resources and that, over time, the socioeconomic differences will diminish. Several possible plausible barriers to take-up can, however, be identified including inadequate information about services, socioeconomic differences in the concepts of health and disagreement about the importance of the service, language differences and the costs of participation 15 – 19. The potential for health promotion activities to increase social inequalities in health has been noted2022 and community development approaches to health promotion have been proposed as one way of building more appropriate interventions 23.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that AAA screening programs in rural or underserved areas can be successful and cost-effective. 20,21 By preventing the rupture before it happens, any discussion about difference in mortality by surgeon specialization becomes moot.…”
Section: Discussionmentioning
confidence: 99%